Erythroplasia of Queyrat treated by laser and light modalities: a systematic review. Issue 9 (December 2016) - Maranda, Eric; Nguyen, Austin; Lim, Victoria; Shah, Vidhi; Jimenez, Joaquin
Abstract Erythroplasia of Queyrat (EOQ) is a squamous cell carcinoma in situ most commonly located on the glans penis or prepuce. EOQ accounts for roughly 10 % of all penile malignancies and may lead to invasive squamous cell carcinoma. Standard therapy includes local excision, partial or total penectomy, cryotherapy, and topical cytotoxic agents. Treatment of EOQ has proven to be challenging due to low response rates and recurrence. In addition, radical procedures can significantly affect sexual function and quality of life. Alternative laser treatments and photodynamic therapy (PDT) offer promising results for treating EOQ. A systemic review of the literature was performed for articles discussing laser and light therapy for EOQ. Among the patients treated with the CO2 laser, 81.4 % of cases had complete remission after one session of treatment. Patients treated with PDT presented with more variable results, where 62.5 % of those treated with methyl aminolevulinate photodynamic therapy (MAL-PDT) achieved complete remission. Aminolevulinic acid (ALA-PDT) treatment showed a similar rate of remission at 58.3 %. One study utilized the Nd:YAG laser, which resulted in a recurrence of the lesion in four of the five patients treated. Of the methods reviewed, the CO2 laser offered the most promising results with a cosmetically excellent prognosis. Further studies with larger power and longer follow-up times are needed to determine the optimal treatment regimen for this penile malignancy.